A new method to reduce delaminations during drilling of FRP laminates by feed rate control. (15th February 2018) - Sorrentino, L.; Turchetta, S.; Bellini, C.
Abstract: Assembling of parts made of composite materials is often obtained by bolted or riveted joints. Therefore, drilling is one of the most common machining operation for composite laminates. However, this process causes some kinds of damage on the laminates, as delamination; the aim of this work is to reduce the delamination of the laminate. First of all, in this paper the influence of cutting parameters on the drilling process was studied for both CFRP and GFRP laminates, focusing the attention on the measurement of the forces acting on the laminate for several values of cutting speed and feed rate. Then both peel-up and push-out delamination factors were evaluated and related to the measured forces. In such manner, harmful sets of cutting parameter, capable of damaging the laminate, were identified. This analysis was useful for defining a new method to reduce push-out delamination, that was introduced and verified.